2019
DOI: 10.2478/jomb-2018-0052
|View full text |Cite
|
Sign up to set email alerts
|

The importance of RET-He in the diagnosis of iron deficiency and iron deficiency anemia and the evaluation of response to oral iron therapy

Abstract: SummaryBackgroundThe purpose of this study is to investigate whether or not reticulocyte hemoglobin equivalent (RET-He) is a superior indicator of blood count and other iron parameters in terms of diagnosing iron deficiency (ID) and iron deficiency anemia (IDA), and thus evaluating a patient’s response to oral iron treatment.MethodsThe research population consisted of 217 participants in total: 54 control, 53 ID, 58 non-ID anemia, and 52 IDA patients. A hemoglobin (Hb) value of < 130.0 g/L was defined as in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 13 publications
4
30
0
4
Order By: Relevance
“…For example, Toki et al revealed that Ret-He may be associated with ID by a sensitivity of 92.0% and a specificity of 81.0% (area under the curve (AUC) = 0.902) using a Ret-He cut-off value of ≤30.9 pg in adults [17]. In another study, Ret-He ≤ 25.4 pg predicted ID in adults with a sensitivity of 90.4% and a specificity of 49.1% [18]. Screening for ID and IDA using Ret-He in context of PBM has been poorly studied, especially in the pediatric surgical population.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Toki et al revealed that Ret-He may be associated with ID by a sensitivity of 92.0% and a specificity of 81.0% (area under the curve (AUC) = 0.902) using a Ret-He cut-off value of ≤30.9 pg in adults [17]. In another study, Ret-He ≤ 25.4 pg predicted ID in adults with a sensitivity of 90.4% and a specificity of 49.1% [18]. Screening for ID and IDA using Ret-He in context of PBM has been poorly studied, especially in the pediatric surgical population.…”
Section: Introductionmentioning
confidence: 99%
“…Values of Ret-He were significantly lower in hypothyroid patients having IDA as compared to controls. Uçar et al [21] conducted a study in which the value of Ret-He was significantly lower in iron deficient groups as compared to control. Our study also showed the value of Ret-He was significantly low in groups with iron deficiency in combination with anemia of chronic disorder and latent iron deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The changes in iron status tests in response to ID, IDA, or iron overload are reported in Table 1. [14,54,55]. The assessment of neonatal iron status is a challenging task as neonatal blood sampling requires a well-trained phlebotomist and is not routinely performed among healthy newborns.…”
Section: Iron Status Measurementmentioning
confidence: 99%
“…The changes in iron status tests in response to ID, IDA, or iron overload are reported in Table 1 . [ 14 , 54 , 55 ].…”
Section: Iron Status Measurementmentioning
confidence: 99%